Methicillin-Resistant Staphylococcus aureus Carriage among Students at a Historically Black University: A Case Study - Hua Shen; Eyitayo Akoda; Kunyan Zhang (International Journal of Microbiology)
Background. Black people in the USA is afflicted with a higher rate of methicillin-resistant Staphylococcus aureus (MRSA) infection. This study determined the prevalence of MRSA carriage among black college students at a university setting. Methods. Hand and nasal swabs were collected and screened for MRSA by mannitol fermentation, coagulase, and DNase activities and their resistance to oxacillin. MRSA isolates were analyzed for antimicrobial resistance pattern, genetic profile for staphylococcal cassette chromosome mec (SCCmec) type, pulsed-field type, multilocus sequence type (ST), and the presence of Panton-Valentine leukocidin (PVL) gene. Results. MRSA was isolated from 1 of the 312 (0.3%) hand swabs and 2 of the 310 (0.65%) nasal swabs, respectively. All isolates lack multidrug resistance and have type IV SCCmec, characteristic of community-associated MRSA. These isolates were a ST8-MRSA-IVa-PVL(+) (USA300 strain), a ST8-MRSA-IVb-PVL(−), and a new MLST, ST2562-MRSA-IV-PVL(−), identified in this study. These isolates were thus not transmitted among students. Conclusion. We found a low rate of MRSA carriage among students in a black university. Our finding highlights the need of future study which involves multiinstitutions and other ethnic group to assess the association of black race with MRSA carriage.